Event-triggered control of networked switched systems under network attacks. (April 2022) - Han, Yuchen; Lian, Jie
This paper is concerned with the event-triggered control (ETC) problem for switched systems in networked environments, which are suffered from denial-of-service (DoS) attack and deception attack. Considering that the packet in networked switched systems contains the sampled state and switching signal, DoS attack prevents the packet transmission to cause the zero input, while deception attack falsifies the packet to cause the asynchronous control input with nonlinear disturbance. First, the probabilistic characterization of invalid packet transmissions caused by two different attack models is constructed, namely the ratio of the number of packet transmissions suffering from network attacks to the total number of packet transmissions. Second, a suitable ETC scheme is designed to determine the next triggering instant, which guarantees that the value of Lyapunov function cannot exceed a given restriction and updates the control input at switching instant. After that, the average dwell time and control gains are designed to guarantee the almost sure asymptotic stability of such systems. Finally, a numerical simulation is given to verify the effectiveness of the theoretical results.